Analisis Strategi Komunikasi Korporasi Badan Pengurus Cabang Perhumas Pekanbaru - Rosmala (Jurnal InterAct, 2024)
Corporate communication refers to the communication process carried out by a company with the aim of establishing and maintaining positive relationships with various stakeholders, both external and internal like customers, investors, government and society, as well as employees. This research aims to analyze the corporate communication strategy of an organization called Perhumas. This research uses qualitative methods with descriptive data analysis. The analysis technique is carried out using observation, interviews and document analysis. The participants in this research were 5 officers of BPC Perhumas Pekanbaru. The research results show that the corporate communication strategies carried out by BPC Perhumas Pekanbaru members consist of (1) Activities carried out to maintain identity, image and reputation; (2) Internal communication system; (3) Media; (4) CSR; (5) Marketing communications; (6) Communication crisis; (7) Relations with investors; (8) Relations with the government. The research conclusion shows that communication strategy can create better relations with the government, collaborate with the media, create a relevant internal communication system, but investor relations and marketing communications need to make improvements to the activity program at BPC Perhumas Pekanbaru maintain corporate communications capabilities to build trust and provide a positive influence on organizational sustainability.